Spontaneous mode locking of a multimode semiconductor laser under continuous wave operation - Chomet, Baptiste; Blin, Stéphane; Beaudoin, Grégoire; Pantzas, Konstantinos; Sagnes, Isabelle; Denet, Stéphane; Garnache, Arnaud (Frontiers in Photonics, 2023)
Self starting modelocking has been observed experimentally for a laser based on a compact III-V diode-pumped quantum-well surface-emitting semiconductor laser technology with a saturable absorber free but dispersive cavity. Continuous wave generation of picosecond pulses at 100 GHz rate is demonstrated by recording microwave intensity noises and beat frequency, time-resolved optical spectra and intensity autocorrelation. Coherence of the pulse train is obtained through frequency noise measurement of the demodulated beat note, demonstrating a timing jitter as low as 110 fs, near quantum limit. Using a theoretical model based on a generalized Haus Master Equation, we demonstrate the existence of this mode locked state without the need of non-linear self amplitude modulation. The fundamental physical mechanism is the interplay between self phase modulation and anomalous dispersion like in cavity soliton together with light matter interaction induced time symmetry breaking.